2019
DOI: 10.1037/ccp0000422
|View full text |Cite
|
Sign up to set email alerts
|

Intensive group behavioral treatment (IGBT) for children with selective mutism: A preliminary randomized clinical trial.

Abstract: Objective: Very few controlled trials have evaluated targeted treatment methods for childhood selective mutism (SM); the availability of evidence-based services remains limited. This study is the first controlled trial to evaluate an intensive group behavioral treatment (IGBT) for children with SM. Method: Twenty-nine children with SM (5-9 years; 76% female; 35% ethnic minority) were randomized to immediate SM 5-day IGBT or to a 4-week waitlist with psychoeducational resources (WLP), and were assessed at Week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 63 publications
3
55
0
1
Order By: Relevance
“…Furthermore, although the children with SM showed a significantly increased speech after treatment, they still lagged behind the TDs. Comparable end points (⩽2) on the SMQ/SSQ after treatment has also been reported in other studies of SM ( Bergman et al, 2013 ; Catchpole et al, 2019 ; Cornacchio et al, 2019 ; Klein et al, 2017 ). At present, we do not know whether a more intensified treatment would increase speech in children with SM, or whether a somewhat reduced level of speech is to be expected in a group of children where behaviorally inhibited temperament is prominent ( Gensthaler et al, 2016 ; Muris et al, 2016 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, although the children with SM showed a significantly increased speech after treatment, they still lagged behind the TDs. Comparable end points (⩽2) on the SMQ/SSQ after treatment has also been reported in other studies of SM ( Bergman et al, 2013 ; Catchpole et al, 2019 ; Cornacchio et al, 2019 ; Klein et al, 2017 ). At present, we do not know whether a more intensified treatment would increase speech in children with SM, or whether a somewhat reduced level of speech is to be expected in a group of children where behaviorally inhibited temperament is prominent ( Gensthaler et al, 2016 ; Muris et al, 2016 ).…”
Section: Discussionsupporting
confidence: 79%
“…Baseline scores below 1 on the SSQ and the SMQ School subscale have largely been supported in data from recent SM treatment studies which include a reasonably large samples of children, in both United States and Europe ( Bergman et al, 2013 ; Catchpole et al, 2019 ; Cornacchio et al, 2019 ; Klein et al, 2017 ; Lang et al, 2016 ; Oerbeck et al, 2014 ) (see Table 1 ). These studies also demonstrate small, but significant changes after treatment (of different lengths) with post-treatment scores ranging from 1 to 3 (generally ⩽2).…”
mentioning
confidence: 75%
“…A preliminary randomized clinical trial into behavioral treatment of selective mutism showed an effect size of Cohen's d = 0.58 on speaking in social situations [ 15 ]. To determine effects on our primary outcome (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…A recent non-randomized trial showed that behavioral techniques with additional parent child interaction therapy improve SM symptoms [ 13 ]. Three previous randomized controlled trials (RCT) investigated showed that behavioral therapy was effective for selective mutism [ 8 , 14 , 15 ]. These studies provided therapy in different settings i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation